Assessment of critical velocity in track and treadmill: Physiological profiles and relationship with 3000-meter performance - Massini, Danilo Alexandre [UNESP]; Caritá, Renato Aparecido [UNESP]; Siqueira, Leandro Oliveira da Cruz [UNESP]; Simionato, Astor Reis [UNESP]; Denadai, Benedito Sérgio [UNESP]; Filho, Dalton Muller Pessôa [UNESP] (FapUNIFESP (SciELO), 2018)
The present study aiming to verify the interference of different conditions (treadmill vs. track) on critical velocity (CV) values, as well as on the correlation to the 3000-meter performance (v3000m), and thus infer about the specificity of each values as training parameter for this distance. Seven runners (15.3±1.4 years) were submitted to a maximal progressive test (1.0 km×h -1 increments per minute until exhaustion) to assess VȮ 2 max and maximal aerobic velocity (vVȮ 2 max). Subsequently, CV was estimated from three running performances at each test condition, with exercise intensities adjusted for different time limits (t Lim ) at 900, 2100 and 3300 meters in track or at 90, 95 and 115% of vVO 2 max in treadmill. From linear adjustments, using stepwise method, CV was assessed on treadmill (CV TREADMILL ) and track (CV TRACK ), and both compared by the Mann-Whitney test.The sample-adjusted dispersion coefficient (R 2 adj ) analyzed the variance of v3000m with CV TRACK , CV TREADMILL and vVȮ 2 max. In all analyses, significance was set at P≤0.05. In progressive test, VȮ 2 max reached 54.2±5.2 mLO 2 ×kg -1 ×min -1 and vVȮ 2 max reached 16.8±1.9 km×h -1 . No differences were observed between CV TREADMILL and CV TRACK (14.0±1.8 vs. 12.3±3.2 km×h -1 , P=0.46). Correlations were observed for v3000m with CV TREADMILL (R 2 adj ~0.94), CV TRACK (R 2 adj ~0.99) and vVȮ 2 max (R 2 adj ~0.90), all showing P=0.001. It could be concluded that no influence was observe on the ability to achieve identical CV values from different assessment conditions. The correlation to the v3000 meters suggested better specificity of CV TRACK than CV TREADMILL for training prescription and performance control.
Avaliação da velocidade crítica de corrida em pista e esteira: Perfis fisiológicos e relações com o desempenho em 3000 metros
Keywords: Athletic performance; Exercise test; Exercise tolerance; Oxygen uptake; Track and field